Productive traits of broiler chickens fed diets containing different growth promoters - Pelicano, ERL [UNESP] (2004)
This study evaluated the effect of different probiotics and prebiotics on the performance of broilers. One-day-old male broiler chicks from the Cobb strain (n=1,260) were randomly distributed in a 3 x 3 factorial arrangement, considering 3 probiotics and 3 prebiotics sources. Nine treatments with 4 repetitions and 35 birds per parcel were used. The results showed that there was no influence of treatment on feed intake at the different rearing phases. Better weight gain (p<0.05) was seen when diet was supplemented with the phosphorylated mannanoligosaccharide-based prebiotic (MOS) compared to diets without prebiotics. Feed conversion of birds fed diets with probiotics and prebiotics was better than feed conversion of birds not receiving such additives. Such better results were seen in the initial period (1 to 21 days), but not in the following period (1 to 35 days) or in the total period (1 to 42 days). Better rearing viability was seen when MOS was used together with organic acidifier when compared to the diets without prebiotic. Viability was worst when no prebiotics or probiotics were used. It was concluded that beneficial effects were seen in performance of birds at 21 days when the growth promoters were used, but not at 42 days of age. Nevertheless, there was better growth viability at 42 days of age when growth promoters were added.